Aggressive Behaviour and Sleep: History, Review, and Perspectives - Pires, Gabriel Natan; Tufik, Sergio; Hoshino, Katsumasa [UNESP]; Levy Andersen, Monica (Springer Nature, 2018)
The relationship between sleep and behaviour has been studied in the context of several fields. It is known that changes in sleep pattern as well as sleep disorders are intimately linked to both cognitive and behavioural co-morbidities, including aggressive behaviour. Although the relationship between sleep and aggression has been examined from different angles, particularly in the past decade, the literature lacks a comprehensive and broad review of findings on the topic. The current review seeks to condense the content of the literature on sleep and aggressive behaviour by bringing the interface of these two themes to light. Herein, first, historical overview on the studies about this relationship is provided. Following, the basic concepts of both themes are presented in a concise manner, thus enabling a critical and summarized discussion regarding the main findings in both laboratory animals and humans concerning the association of sleep and aggressive behaviour. Finally, the main perspectives in this field of research are highlighted. Based on the reviewed studies, it becomes plausible to conclude that sleep deprivation induces aggression in several contexts. The opposite relationship, aggressive behavioural phenotype inducing changes in sleep parameters, is applicable in a lower extent. Despite the need for additional investigations into the subject, this review summarized the knowledge that exists on the relationship between sleep and aggressive behaviour, pointing out its neurobiological relevance.
Keywords: Aggression; Aggressive behaviour; Sleep